Physical and chemical data from a firn aquifer in Southeast Greenland, 2015-2016 - Olivia Miller; Kip Solomon; Clement Miege; Richard Forster; Lora Koenig (Arctic Data Center, 2019)
This dataset includes physical and chemical data from a firn aquifer upslope from Helheim Glacier collected in 2015 and 2016 to advance understanding of aquifers forming within the firn (compacted snow) of the percolation zone off the Greenland ice sheet. The dataset includes depth-specific tritium and Chlorofluorocarbon-11 (CFC-11) measurements in aquifer liquid water and tritium in firn, dye concentration from a tracer experiment, and firn core stratigraphy. The tritium and CFC-11 data constrain aquifer age. The dye experiment provides information on meltwater movement through the unsaturated zone. Firn stratigraphy provides insight into snow accumulation and compaction, as well as melt patterns.